Transformasi geostrategi Indonesia di tengah perubahan tatanan geopolitik global - Virdaos, Virly Jihan Naoura (Maliki Interdisciplinary Journal, 2026)
Global geopolitical developments in the 21st century have significantly impacted Indonesia's national resilience. With globalization, technological advancements, inter-state competition, and non-military threats such as cybercrime and radicalism, Indonesia needs to develop a national strategy that can adapt sustainably. This study aims to examine how Indonesia's geostrategy has evolved in response to changes in the global geopolitical order and strengthen national resilience. This study employed a literature review method, reviewing various journals and literature on geopolitics, geostrategy, and Indonesia's national resilience. The results show that Indonesia's strategic location in the Indo-Pacific region offers numerous opportunities, particularly in the fields of economics, trade, and international diplomatic relations. However, this location also presents numerous challenges, particularly in maritime security, such as piracy and territorial conflicts. Therefore, Indonesia needs to strengthen the values ​​of Pancasila, improve the quality of human resources, develop digital literacy, modernize its defense system, and strengthen regional cooperation through ASEAN. In this way, Indonesia can maintain national sovereignty and stability. To achieve this, synergistic cooperation is needed between the government, society, and national institutions to strengthen Indonesia's national resilience amidst the ever-evolving global geopolitical dynamics.